2017
DOI: 10.1093/ee/nvw174
|View full text |Cite
|
Sign up to set email alerts
|

CandidatusLiberibacter solanacearum” Associated With the Psyllid,Bactericera maculipennis(Hemiptera: Triozidae)

Abstract: The psyllid Bactericera maculipennis (Crawford) (Hemiptera: Triozidae) often cohabits field bindweed (Convolvulus arvensis, Solanales: Convolvulaceae) and other plants with the congeneric psyllid, Bactericera cockerelli (Šulc), in the Pacific Northwestern United States. Bactericera cockerelli is a vector of "Candidatus Liberibacter solanacearum," the pathogen associated with zebra chip disease of potato (Solanales: Solanaceae). Because B. maculipennis and B. cockerelli both naturally occur on certain plants, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Similarly, specific associations between B. cockerelli biotypes and Ca. L. psyllaurous sequence types have not been established, and there are few studies exploring possible alternative vectors in the North American range (but see 26 ) despite novel Ca. L. psyllaurous-psyllid associations existing in Europe (e.g., haplotypes C and U in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, specific associations between B. cockerelli biotypes and Ca. L. psyllaurous sequence types have not been established, and there are few studies exploring possible alternative vectors in the North American range (but see 26 ) despite novel Ca. L. psyllaurous-psyllid associations existing in Europe (e.g., haplotypes C and U in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Liberibacter species was assembled from this study (Ca. L. psyllaurous haplotype G) and from 9,[24][25][26][27][28][29][30][31][32][33][34]74 . Designed by Authors from Flaticon and Pixbay with license permission.…”
mentioning
confidence: 99%
“…Transmission by these 2 psyllid species has not been tested yet. 'Candidatus L. europaeus' was detected in 9 Cacopsylla species (Camerota et al, 2012) and in Arytainilla spartiophila (Thompson et al, 2013), and CLso was found associated with different Bactericera species (Teresani et al, 2015;Borges et al, 2017). As the interactions between different Liberibacter species and psyllids are studied, a better understanding Hansen et al, 2008; of the effects of these pathogens on the vector will be obtained.…”
Section: The Effect Of Bacterial Pathogens On the Insect Vectormentioning
confidence: 99%
“…Haplotypes A and B appear to be most commonly associated Solanaceous crops in the United States (Dahan et al, 2017(Dahan et al, , 2019 with CLso haplotype B causing more severe symptoms than haplotype A (Mendoza-Herrera et al, 2018;Swisher-Grimm et al, 2018;Harrison et al, 2019;Tang et al, 2020). This pathogen infects multiple psyllid vectors within the Triozidae (Munyaneza et al, 2010;Tahzima et al, 2014;Antolinez et al, 2017;Borges et al, 2017), but is transmitted among Solanaceous plants by the potato psyllid (Bactericera cockerelli; Triozidae) in North America (Munyaneza et al, 2007;Hansen et al, 2008;Liefting et al, 2009). Like CLas, CLso is transmitted in a circulative and propagative manner, and colonization of the vector's salivary glands by CLso is required for transmission to new host plants (Cooper et al, 2014;Sengoda et al, 2014).…”
Section: Introductionmentioning
confidence: 99%